Speech Culture of Lawyers in the Texts of Documents - Olha Podolianchuk (Pedagogical Discourse, 2024)
The article examines the issue of lawyers' speech culture, defines the role of lawyers' speech culture in the texts of documents. The culture of speech is one of the priorities of the national revival of Ukrainian culture in general, because language is not only a carrier of information, but also a driver in solving all issues and in raising the culture and spirituality of the people. Therefore, knowledge of the Ukrainian language and its use in the professional sphere is not only a guarantee of mutual understanding, but also a lawyer's business card, because the lawyer's literacy and education, his ability to submit material in accordance with language norms and standards are the key to success in every case. Recommendations are offered to improve the level of speaking culture of lawyers in the texts of documents, in particular: mastering the literary norms of the modern Ukrainian language in accordance with the current spelling, forming the skills of the culture of the written language, the ability to accurately, logically and consistently, concisely and expressively, in accordance with the conditions of communication, express one's own opinions, convey the necessary information, improve the communication skills and skills of speakers and create the texts of documents. It is noted that the speech culture of a lawyer in the texts of documents is not only a representative of his linguistic and communicative capabilities, but also a representative of his professional and personal skills and abilities, because the text of the document not only requires compliance with certain rules regarding its drafting, but also knowledge of the norms of the literary language, the ability to use language clichés, clearly and correctly formulate an opinion, accurately and logically present the material, as well as adhere to ethical rules for composing relevant texts.